1985
DOI: 10.1111/j.1365-2559.1985.tb02844.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal biopsy of vascular ectasia (angiodysplasia) of the large bowel detected during routine colonoscopic examination

Abstract: Between 1975 and 1983, 9434 colonoscopic examinations were performed at the University Hospital of Zürich. Localized vascular ectasia was detected in 84 patients and there were 48 mucosal biopsies from 46 patients. From the total of 48 biopsies only 24 (50%) showed vascular anomalies. The most frequent lesion encountered was groups of thin-walled dilated vessels in the lamina propria seen in 21 biopsies from 20 patients. These dilated vessels are not specific but in respect of age (median 69 years), location (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Similar to our case, endoscopic biopsy is generally of low diagnostic yield as significant histological abnormalities are submucosal in angiodysplasia 12. Histologically, these lesions consisted of dilated, distorted, tortuous, thin-walled vessels that were lined by endothelium, with little or no smooth muscle and no inflammation, fibrosis, or atherosclerosis 13.…”
Section: Discussionsupporting
confidence: 71%
“…Similar to our case, endoscopic biopsy is generally of low diagnostic yield as significant histological abnormalities are submucosal in angiodysplasia 12. Histologically, these lesions consisted of dilated, distorted, tortuous, thin-walled vessels that were lined by endothelium, with little or no smooth muscle and no inflammation, fibrosis, or atherosclerosis 13.…”
Section: Discussionsupporting
confidence: 71%
“…Stamm et al 19 concluded that this finding confirms the endoscopic diagnosis of vascular ectasia, but it must be emphasized that ectatic vessels may be present in the lamina propria with other conditions, such as diverticulosis, 20 in the stalk of an adenomatous polyp, and at an anastomotic site.…”
Section: P Resentation Of C Asementioning
confidence: 66%
“…Histologically, angiodysplasia resembles telangiectasia, and is characterized by dilated and tortuous vessels. 16) Intracranial aneurysm associated with angiodysplasia is rarely reported. 2,7) The present case has several unique points: two large intracranial aneurysms identified at a young age (21 years); association of nevi, which were histologically confirmed as angiodysplasia; and revascularization after surgical occlusion within a short time (11 days).…”
Section: Discussionmentioning
confidence: 99%